The Resurrection of Jesus: A Clinical Review of Psychiatric Hypotheses for the Biblical Story of Easter - Bergeron, Joseph W. (Irish theological quarterly, 2015)
Jesus’ resurrection to bodily life after death by crucifixion is foundational to orthodox Christianity. The disciples had encounters with Jesus after his crucifixion which caused them to believe he had been bodily resurrected to life again. Psychiatric hypotheses have been proposed as naturalistic explanations for his disciples’ beliefs, which include hallucinations, conversion disorder, and bereavement experiences. Since they propose hallucinatory symptoms that suggest the presence of underlying medical pathology, clinical appraisal of these hypotheses for the disciples’ encounters with the resurrected Jesus is warranted. Psychiatric hypotheses for the disciples’ belief in Jesus’ resurrection are found to be inconsistent with current medical understanding and do not offer plausible explanations for the biblical story of Easter.